PENGARUH EFISIENSI KERJA DAN ETOS KERJA TERHADAP PRODUKTIVITAS KERJA DENGAN SELF EFFICACY SEBAGAI INTERVENING PADA INSTRUKTUR BBPVP BEKASI. - Risdan Sudarmaji; Mochamad Sarif Hasyim; Doni Mardiyanto (JURNAL ILMIAH EDUNOMIKA, 2026)
The industry 4.0 revolution fundamentally transform workforce competency requirements and vocational training management. Psychological aspects, particulary self-efficacy play a crucial role in explaining work productivity variations among vocational instructors. This research examine the influence of work efficiency and work ethic on work productivity with self-efficacy as an intervening variable among instructors at BBPVP Bekasi. This quantitative research employed a survei method using questionnaires distributed to 118 instructors selected through Slovin formula samping. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) encompassing outer model evaluation and inner model testing. Findings reveal that work efficiency significantly influences both self-efficacy and work productivity. Work ethic significantly affects self-efficacy but does not directly influence productivity. Self-efficacy significantly impacts work productivity and successfully mediates the relationship between work efficiency and productivity. However, self-efficacy does not significantly mediate the work ethic–productivity relationship. The model explains 57.9% of self-efficacy variance and 66.9% of productivity variance, with predictive relevance. Enhancing instructor productiviy requires not only technical efficiency and work ethic but also psychological empowerment through self-efficacy strenghtening. Work efficiency exert both direct and indirect effect via self-efficacy, while work ethic operates primarily through self-efficacy to influence productivity. these findings contribute theoretically to human resource management literature and provide practical implications for vocational training institutions in designing sustainable instructor development programs. Keywords: work efficiency, work ethic, self-efficacy, work productivity, vocational instructors.